2015
DOI: 10.1186/s40814-015-0034-y
|View full text |Cite
|
Sign up to set email alerts
|

A pragmatic pilot randomized trial to investigate the effectiveness of behavioural activation group therapy in reducing depressive symptoms and improving quality of life in patients with depression: the BRAVE pilot trial protocol

Abstract: BackgroundDepression is a common disorder with a lifetime prevalence of 16 %. Despite the availability of several treatment options for depression, many patients do not respond to treatment and develop chronic illness associated with several secondary comorbidities. Behavioural activation (BA) is a simple therapy that has the potential for improving symptoms of depression and quality of life in patients with depression. The effectiveness of BA has not, however, been tested in a group format for patients with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…This trial has been registered with ClinicalTrials.gov (identifier #NCT02045771) and was approved by the Hamilton Integrated Research Ethics Board (HIREB: 14-042). The protocol for this trial is published in Pilot and Feasibility Studies [20]. The reporting of this pilot trial is in accordance with the CONSORT extension for randomized pilot and feasibility trials [21,22].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This trial has been registered with ClinicalTrials.gov (identifier #NCT02045771) and was approved by the Hamilton Integrated Research Ethics Board (HIREB: 14-042). The protocol for this trial is published in Pilot and Feasibility Studies [20]. The reporting of this pilot trial is in accordance with the CONSORT extension for randomized pilot and feasibility trials [21,22].…”
Section: Methodsmentioning
confidence: 99%
“…A block randomization system with block sizes of 2, 4, and 6 randomly assigned allocations; the randomization schedule was computergenerated. Full details of the randomization assignment, concealment, and other trial-related methods are described in the protocol [20]. Ten participants were recruited to each arm of the study, which was decided based on the recommended therapy group size of 6-12 [20].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study will combine multiple designs (pilot study, pragmatic trial, mixed methods study), as previously reported by Samaan et al 33. This will allow for the flexibility needed to study multiple dimensions of a new programme, especially one designed for creating healthy lifestyles through the development of participant-directed goals and individualised action plans 43–46.…”
Section: Methods and Analysismentioning
confidence: 99%
“…This person-centred approach is not mainstream in the clinical setting and few individuals have access to behavioural therapists. Furthermore, many current available services and research studies address only one condition or patient population, exclude those who cannot participate in pre-set physical activity or exercise programmes, focus only on secondary or tertiary prevention, or neglect the role of mental health or the determinants of health in lifestyle changes 33–35. A new, multidisciplinary, person-centred, and evidence-based and practice-based healthy lifestyles programme has been created to address these needs 36.…”
Section: Introductionmentioning
confidence: 99%